Enhancement of mechanical properties of high modulus polypropylene grade for multilayer sewage pipes applications. Issue 3 (5th November 2022) - Khoury Moussa, Helena; Challita, Georges; Badreddine, Houssem; Montay, Guillaume; Guelorget, Bruno; Vallon, Thomas; Yared, Wadih; Abi Rizk, Marwan; Alhussein, Akram
Abstract: Advances in technology have provided fresh generations of stiff polypropylene block copolymers for gravity sewerage applications. The aim of this study is to further enhance the stiffness of these materials through the incorporation of inorganic fillers. In this study, three talc filled PP and one glass fiber filled PP composites were characterized in order to be used as a middle layer in a three‐layer sewage pipe. The obtained results showed an increase of approximately more than 100% and 250% in tensile and flexural moduli by the use of 30%–50 wt% talc‐filled PP and 30 wt.% glass fiber‐filled PP, respectively. This high increase in the rigidity of the material would allow manufacturing pipes with improving ring stiffness. Composites filled with 30 wt% talc or glass fiber showed good filler‐matrix interaction and good filler distribution and dispersion. However, reduced filler‐matrix interaction was observed in the case of the composite filled with 50 wt% talc. In addition, the use of Differential Scanning Calorimetry analysis revealed that the addition of fillers enhanced the crystallization temperature of the polypropylene matrix. Furthermore, Thermogravimetric Analysis showed that the high modulus PP grade retained its thermal stability in the various composites. Abstract : Improvement of the ring stiffness of a plain pipe by the development of a multilayer composite pipe.